The mediating effect of traffic safety climate between pedestrian inconvenience and pedestrian behavior. (October 2018) - Xu, Jing; Ge, Yan; Qu, Weina; Sun, Xianghong; Zhang, Kan
Highlights: Pedestrians' perceived inconvenience is an important factor that affects pedestrian behavior. The influence of pedestrians' perceptions of the traffic safety climate cannot be disregarded. Functionality fully mediated the effect of inconvenience pedestrians perceive in city traffic on transgressive behavior. Abstract: Because most people are pedestrians at some point on any given day and walking is the most indispensable means of transportation, pedestrian safety should be investigated. The primary aim of this study was to investigate the relationships among the inconveniences that pedestrians perceive in city traffic, the traffic safety climate and pedestrian behavior. A total of 311 participants voluntarily and validly completed a survey that included the Pedestrian Inconvenience Questionnaire (PIQ), the Traffic Climate Scale (TCS) and the Pedestrian Behavior Scale (PBS). We discovered that pedestrians' perceived inconvenience was positively correlated with transgression and positive behavior by pedestrians and it also positively correlated with the external affective demands (emotional engagement facet of TCS) while negatively correlated with the functionality (functional traffic system facet of TCS). We determined that the external affective demands were positively correlated with pedestrian risk behaviors (i.e., transgression, aggressive behaviors and lapses), internal requirements (traffic participants' skills facet of TCS) were positively correlated with positive behaviors, and functionality was negatively correlated with transgression and lapses. Moreover, the results indicate that the relationship between the inconveniences pedestrians perceive in city traffic and pedestrians' transgressive behavior was fully mediated by the functionality dimension of the traffic safety climate. Pedestrians' perceived inconvenience is an important factor that affects pedestrian behavior, and the influence of pedestrians' perceptions of the traffic safety climate cannot be disregarded.